The incidence of turnip yellows virus in oilseed rape crops (Brassica napus L.) in three different regions of England over three consecutive growing seasons and the relationship with the abundance of flying Myzus persicae. (26th February 2020) - Asare‐Bediako, Elvis; Jones, Julie E.; Hambidge, Angela J.; Stevens, Mark; Mead, Andrew; Jenner, Carol E.; Walsh, John A.
Abstract: Turnip yellows virus (TuYV) is the most important virus infecting oilseed rape in the United Kingdom. The incidence and spatial distribution of TuYV in winter oilseed rape (WOSR) crops in three regions of England were determined over three growing seasons. Leaf samples were collected from three fields in each region, in autumn (November–December) and spring (April) of the three crop seasons and tested for virus presence by enzyme‐linked immunosorbent assay. Infection was detected in all fields except one. Higher TuYV incidences were recorded in 2007–2008 (≤89%) and 2009–2010 (≤100%) crop seasons than in 2008–2009 (≤24%). Highest incidences were recorded in Lincolnshire (≤100%), followed by Warwickshire (≤88%), with lowest incidences in Yorkshire (1–74%). There was a significant increase in incidence detected between autumn and spring sampling in eight fields, a significant decrease in one field and no significant change in 18 fields. Rothamsted Insect Survey suction trap data for the aphid Myzus persicae in Lincolnshire, Warwickshire and Yorkshire revealed two peaks of flight activity in most years (2007–2009). The second peak (September–November) coincided with emergence of WOSR. The highest cumulative (August–November) trap catches in the three regions during the three crop seasons occurred in Lincolnshire and the lowest in Yorkshire; catches in autumn 2009 were highest and lowest in autumn 2008. Regression analysis revealed a highly significant association between the cumulative numbers of M. persicae caught in the suction traps closest to the crops between August and November each year and the incidence of TuYV detected in the WOSR crops in the autumn of each year. Results are discussed in the light of factors affecting the spread of TuYV and future possibilities for control. Abstract : Turnip yellows virus infection levels in winter oilseed rape were very high in some years in the United Kingdom. Over the 3 years of our study, infection levels varied in different years and between different regions. There was a very close relationship between the cumulative numbers of Myzus persicae aphids caught in Rothamsted Insect Survey suction traps from August to November in each of three regions of England and the incidence of turnip yellows virus in winter oilseed rape fields in the three regions.